Sensitized IR luminescence in Ca3Y2Ge3O12: Nd3+, Ho3+ under 808 nm laser excitation. Issue 6 (15th April 2018) - Baklanova, Yana V.; Enyashin, Andrey N.; Maksimova, Lidiya G.; Tyutyunnik, Alexander P.; Chufarov, Alexander Yu.; Gorbatov, Evgeny V.; Baklanova, Inna V.; Zubkov, Vladimir G.
Abstract: A promising series of infrared phosphors Ca3 Y2- х - y Nd x Ho y Ge3 O12 ( x = 0.0–0.3; y = 0.000015–0.15) with garnet structure has been prepared using a liquid-phase precursor method. The room temperature X-ray powder diffraction study and density functional theory (DFT) calculations show consistently that incorporated trivalent neodymium ions occupy calcium dodecahedral sites, whereas ousted part of calcium ions moves into yttrium/holmium octahedral sites. DFT calculations and results of diffuse reflectance measurements reveal that an increase in the neodymium concentration and, consequently, the degree of cation substitution leads to a noticeable band gap reduction. The infrared luminescence in range from 1.0 to 3.4 µm for Ca3 Y2- х - y Nd x Ho y Ge3 O12 is observed under 808 nm laser diode excitation. The trace amount of holmium ions and a low doping ratio of Ho 3+ and Nd 3+ ions allow revealing of intense emission at 2.0–3.4 µm region. The highest emission intensity is attained at x = 0.15 in Ca3 Y2- х Nd x Ge3 O12 :Ho 3+ . The concentration quenching of Ho 3+ emission in the Ca3 Y1.85–y Nd0.15 Ho y Ge3 O12 solid solutions is observed at the activator content of y > 1.5·10 −4 . A very weak red upconversion emissions at 650 and 740 nm were observed upon 808 nm laser diode excitation. The proposed mechanism for multistage process of energy transfer between the active centers involves the participation of Nd 3+ ions as sensitizers of infrared luminescence of Ho 3+ ions. The results indicate that the Ca3 Y2- х - y Nd x Ho y Ge3 O12 germanate can be considered as a promising material for near- and middle infrared phosphors.